A semi-Lagrangian method for the direct numerical simulation of crystallization and precipitation at the pore scale - Perez, Sarah; Etancelin, Jean-Matthieu; Poncet, Philippe (Frontiers in Earth Science, 2025)
This article introduces a new efficient particle method for the numerical simulation of crystallization and precipitation at the pore scale of real rock geometries extracted by X-Ray tomography. It is based on the coupling between superficial velocity models of porous media, Lagrangian description of chemistry using Transition-State-Theory, involving underlying grids. Its ability to successfully compute dissolution process has been established in the past, and is presently generalized to precipitation and crystallization by means of adsorption modeling. Numerical simulations of mineral CO2 trapping are provided, showing evidence of clogging/non-clogging regimes, and one of the main results is the introduction of a new non-dimensional number needed for this characterization.